KARAKTERISTIK IBU PENDERITA KEHAMILAN EKTOPIK TERGANGGU (KET) DI RSUP HAJI ADAM MALIK MEDAN TAHUN 2010-2015 - Hotmian Sara Zevo Tamba; Fazidah Siregar; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Ectopic Pregnancy (EP) is one of the abortion cause, that impact of maternal death. This is descriptive study with case series design, data analyzed by using the Exact Fisher,Mann Whitne.Kruskal Wallis.The aims to identify characteristics of mothers who are suffering from EP at the H Adam Malik General Hospital, Medan in the 2010-2015 period. The population consisted of 110 persons and being the total sampling. The result show that 66,4% was in the age group of 20-39 years, 37.3% was of the Javanese tribe, 72.7% housewives 53.6% Senior High School by education. Most sample with age of pregnancy 4-8 weeks, multiparity 46,4%, location tuba 78,2%, most complaints of pain in stomach 56,4%, anemia 86.4%. Laparotomy + Salphyngectomy procedures 98,2%, referral origin, direct / no 60,0%, leaving hospital healed/ leaving hospital as outpatient 90.9%,average length of stay 6.3 days. Highest proportion medicine procedures based on ectopic pregnancy location is ovarial, cervical, abdominal, and intraligamenter. There was no significant proportion between medicine procedures and pregnancy age  of pregnancy p = 0.1; There was significant between average length of stay and medicine procedures p=0,044: There was no significant between average length of stay and condition at leaving hospital  p = 0.336. It was recomended pregnant mothers with complaint of stomach pain was suggested to have their pregnancy examined as early as possible at the Hospital. For hospital H.Adam Malik General Hospital, Medan to complete medical record files,especially previous disease history and bad pregnancy history. Key Words: Ectopic Pregnancy, Patient Characteristic